Training for landing and cutting stability in young female basketball and soccer players - Howell, K. C (Strength and Conditioning Journal, 2013)
Anterior cruciate ligament (acl) injuries in female athletes often are not a result of physical contact, rather injuries tend to occur during landing, cutting, or pivoting to change direction or speed. Female basketball and soccer athletes tend to exhibit biomechanical and neuromuscular patterns during these maneuvers, which contribute to their higher incidence of acl injuries among female and male athletes participating in the same sport. However, injury prevention programs that incorporate neuromuscular, plyometric, strength, and balance training have been beneficial in reducing injury risk factors and promoting proper biomechanics to promote knee stability by decreasing stress on the acl during these maneuvers.